Large-scale vortices and zonal flows in spherical rotating convection. (16th February 2021) - Lin, Yufeng; Jackson, Andrew
Abstract: Abstract : Motivated by understanding the dynamics of stellar and planetary interiors, we have performed a set of direct numerical simulations of Boussinesq convection in a rotating full sphere. The domain is internally heated with fixed temperature and stress-free boundary conditions, but fixed heat flux and no-slip boundary conditions are also briefly considered. We particularly focus on the large-scale coherent structures and the mean zonal flows that can develop in the system. At Prandtl number of unity, as the thermal forcing (measured by the Rayleigh number) is increased above the value for the onset of convection, we find a relaxation oscillation regime, followed by a geostrophic turbulence regime. Beyond this we see for the first time the existence of large-scale coherent vortices that form on the rotation axis. All regime boundaries are well described by critical values of the convective Rossby number $Ro_c$, with transitions from oscillatory to geostrophic turbulence, and then to the large-scale vortex regime at values $Ro_c≈ 0.2$ and $Ro_c≈ 1.5$, respectively. The zonal flow is controlled by the convective Rossby number and changes its direction when the flow transitions from the geostrophic turbulence regime to the large-scale vortex regime. While the non-zonal flow speed and heat transfer can be described by the so-called inertial scaling in the geostrophic turbulence regime, the formation of large-scale vortices appears to reduce both the non-zonal flow speed and the efficiency of convective heat transfer.